How breast cancer chemotherapy increases the risk of leukemia: Thoughts about a case of diffuse large B-cell lymphoma and leukemia after breast cancer chemotherapy. Issue 2 (1st February 2016) - Zhang, Bin; Zhang, Xia; Li, Minghuan; Kong, Li; Deng, Xiaoqin; Yu, Jinming
ABSRTRACT: The latest studies suggest that prophylactic chemotherapy or adjuvant chemotherapy for early stage breast cancer may increase the leukemia risk in patients. For patients with a low risk for breast cancer recurrence, physicians who make the choice for adjuvant therapy should consider the risk of its long-term side effects. Is the occurrence of lymphatic system cancer and leukemia after breast cancer treatment associated with chemotherapy? Can these types of leukemia be classified as therapy-related leukaemias? We believe that there may be correlations between any diseases, butwe cannot rush to conclusions or dismiss a correlation because we understand little about the diseases themselves.In this paper, we present a case of secondary diffuse large B-cell lymphoma and leukemia in patients after breast cancer chemotherapy, it is undeniable that this is a special event. For two distinct tumouroccurrences at different times, we cannot give a clear explanation because of thechanges in the genes that might link them together and we hope to attract the attention of other clinicians.